METHODS OF DEVELOPING CORRECT PERCEPTION AND ARTICULATION SKILLS IN FOREIGN LANGUAGE LEARNING - Nina L. Goncharova (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the optimal methods of training the English-language perceptive and articulatory skills within the system approach. It gives the theoretical grounds for selecting mono- / multifunctional exercises aiming at forming analytical perceptive and articulatory skills and synthetic phonetic abilities. The hierarchical receptive, reproductive and productive exercises presented in the article have proved their efficiency in the process of developing foreign language phonetic and phonological competency.